Wilderness defender - Black, Maggie K. (Love inspired suspense., 2021)
With murderous poachers targeting rare blue bear cubs, Alaska trooper Poppy Walsh and her K-9 partner, Stormy, will do whatever it takes to stop them. But having to team up with ex-fiancé, park ranger Lex Fielding will be Poppy's biggest test. When the poachers go after Lex's young son, can Poppy and Lex overcome their unresolved past...and survive a killer's sights?.